The Effects of Acceptance and Commitment Therapy for Couples on Marital Adjustment in Men with Bipolar II Disorder - مصطفی عرب ورنوسفادرانی; مریم‌ فاتحی‌زاده; فاطمه بهرامی; رضوان ‌السادات جزایری; امراله ابراهیمی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: The aim of present study was investigating the efficacy of acceptance and commitment therapy (ACT) for couples on marital adjustment in men with bipolar II Disorder. Methods and Materials: Participants (3 couples) were selected using purposeful sampling. Nonconcurrent multiple baseline experimental single subject study was used as the method. The efficacy of couples’ ACT protocol was carried out in three phases of intervention (baseline, 12-session treatment and 3-month follow-up) by using dyadic adjustment scale (DAS). Data were analyzed by visuals analysis and percentage of non-overlapping data (PND) and percentage of overlapping data (POD) strategies. Findings: There was a significant difference between the mean values of the baseline and intervention scores. The effectiveness of couples-based ACT in men with bipolar II disorder was validated to improve the marital adjustment. Conclusions: ACT for couples can improve the marital adjustment in men with bipolar II disorder and decrease the rate of divorce.